Regulatory effects of estetrol on the endothelial plasminogen pathway and endothelial cell migration. (May 2017) - Montt-Guevara, Maria Magdalena; Palla, Giulia; Spina, Stefania; Bernacchi, Guja; Cecchi, Elena; Campelo, Adrian Esteban; Shortrede, Jorge Eduardo; Canu, Alessio; Simoncini, Tommaso
Highlights: Estetrol (E4) controls endothelial protein levels of plasminogen-activator inhibitor-1 (PAI-1), urokinase-type plasminogen activator (u-PA) and tissue plasminogen activator (t-PA) proteins. Estetrol can interfere with the effects of estradiol in human umbilical vein endothelial cells (HUVEC) but this is dependent on the amount of estradiol present. Estetrol and estradiol modulate c-Fos and c-Jun expression. Plasminogen-activator inhibitor-1 (PAI-1), urokinase-type plasminogen activator (u-PA) and tissue plasminogen activator (t-PA) are required for estetrol-induced endothelial cell migration. Abstract: Background: Estetrol (E4) is a natural estrogen produced solely during human pregnancy. E4 is suitable for clinical use since it acts as a selective estrogen receptor modulator. In clinical trials E4 has been seen to have little or no effect on coagulation. Hence, it is interesting to investigate whether E4 alters endothelial-dependent fibrinolysis. Objectives: We studied the effects of E4 on the fibrinolytic system and whether this could influence the ability of endothelial cells to migrate. In addition, we compared the effects of E4 with those of 17β-estradiol (E2). Study design: Human umbilical vein endothelial cells (HUVEC) were obtained from healthy women. Expression of plasminogen-activator inhibitor-1 (PAI-1), urokinase-type plasminogen activator (u-PA) and tissue plasminogen activator (t-PA) proteins was evaluated by Western blot analysis. Endothelial cell migration was studied by razor-scrape horizontal and multiwell insert systems assays. Results: E4 increased the expression of t-PA, u-PA and PAI-1 in HUVEC, but less so than did equimolar amounts of E2. The effects of E4 on t-PA, u-PA and PAI-1 were mediated by the induction of the early-immediate genes c-Jun and c-Fos. E4 in combination with E2 antagonized the effects induced by pregnancy-like E2 concentrations but did not impair the effects of postmenopausal-like E2 levels. We also found that the increased synthesis of PAI-1, u-PA and t-PA induced by E2 and E4 is important for horizontal and three-dimensional migration of HUVEC. Conclusions: These results support the hypothesis that E4 acts as an endogenous selective estrogen receptor modulator (SERM), controlling the fibrinolytic system and endothelial cell migration.